2012
DOI: 10.1063/1.3680560
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-variational coupled cluster theory

Abstract: Interaction-induced dipoles of hydrogen molecules colliding with helium atoms: A new ab initio dipole surface for high-temperature applications JCP: BioChem. Phys. 6, 01B616 (2012) Interaction-induced dipoles of hydrogen molecules colliding with helium atoms: A new ab initio dipole surface for high-temperature applications J. Chem. Phys. 136, 044320 (2012) A theoretical study of the CX2N radicals (X = F, Cl, Br): The effect of halogen substitution on structure, isomerization, and energetics J. Chem. Phys. 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 66 publications
2
53
0
Order By: Relevance
“…Recently, an O(r 4 )-scaling p2-RDM method 53,54 has been developed through tensor expansions of the excitations 2 T and the twoelectron integrals in the reduced Hamiltonian 2 K. Several pair correlation methods related to the p2-RDM method have also recently been developed. [55][56][57] …”
Section: B Energy Functional With N-representability Conditionsmentioning
confidence: 98%
“…Recently, an O(r 4 )-scaling p2-RDM method 53,54 has been developed through tensor expansions of the excitations 2 T and the twoelectron integrals in the reduced Hamiltonian 2 K. Several pair correlation methods related to the p2-RDM method have also recently been developed. [55][56][57] …”
Section: B Energy Functional With N-representability Conditionsmentioning
confidence: 98%
“…Orbital optimized post‐Hartree–Fock (HF) methods, such as the coupled‐cluster doubles (CCD), active space and excited state CC methods, the second‐order perturbation theory (MP2), the third‐order perturbation theory (MP3), the coupled pair functional theories, the linearized coupled‐cluster doubles (LCCD), and the density‐cumulant functional theory (DCFT), have been reported in previous studies. Triples corrections for the orbital‐optimized CCD method have also been implemented . In the previous studies it has been shown that the OCC and OMP methods are quite beneficial for chemical systems with problematic electronic structures, such as symmetry‐breaking problems, transition states, free radicals, bond‐breaking problems, weak interactions, and predictions of the chemical reactivity .…”
Section: Introductionmentioning
confidence: 99%
“…The approach retains the N 6 cost scaling of CCSD, but with an increased prefactor, because of additional matrix transformations, and additional N 5 work associated with multiple integral transformations arising from the orbital variations. For full details, see [11]. In previous publications, the QV methods compared favourably with multireference methods where CCSD(T) has failed dramatically [13].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few years, several single-reference methods has been developed to tackle inherently multireference systems [9,10]. One such family of methods is quasi-variational coupledcluster doubles, hereafter collectively denoted as the QV methods [11,12]. At the single and double excitation levels, standard CCSD is replaced by the 'quasi-variational' approximation to variational coupled cluster with double excitations, combined with variational optimisation of the energy functional with respect to variations in the reference orbitals (OQVCCD).…”
Section: Introductionmentioning
confidence: 99%